Upaya Meningkatkan Hasil Belajar Kimia Siswa melalui Model Pembelajaran Kooperatif Tipe Scrip di Kelas XII. IPA.I SMAN 2 Lengayang - Srina Nengsih (Departement of Mathematics Education, 2023)
This study aims to disclose information and discuss Efforts to Improve Students' Chemistry Learning Outcomes Through the Scrip Type Cooperative Learning Model in Class XII. IPA.1 SMAN 2 Lengayang. This type of research is classroom action research (CAR). This research was conducted at SMAN 2 Lengayang, Pesisir Selatan District. The subjects of this study were students of class XII. IPA.1 SMAN 2 Lengayang, totaling 29 people. This research will be carried out in the odd semester of the 2022/2023 school year. The research procedure consisted of two cycles with two meetings in each cycle. Each cycle consists of four stages of research namely planning, implementation, observation and reflection. Data collection in this study was carried out using field note techniques, student worksheets, written tests, observation and documentation. Data analysis techniques use percentage formulas and data reduction. From this research, the learning outcomes of class XII.IPA students were obtained. I SMAN 2 Lengayang Academic Year 2022/2023 with Cooperative media Scrip types in Chemistry learning, this can be seen in Cycle I the average student learning achievement was 80.86 with 62% of students who completed 62% or 18 out of 29 students. In Cycle II, the average student learning outcomes were 84.55 with the number of students who completed 25 of the 29 students. Based on the results of this study indicate that the Scrip Type Cooperative Learning Model can improve students' chemistry learning outcomes by giving gifts.